Impact of consumer behavior on furan and furan-derivative exposure during coffee consumption. A comparison between brewing methods and drinking preferences. (30th January 2019) - Rahn, Anja; Yeretzian, Chahan
Highlights: Brewing method has a significant influence on furan and furan derivative exposure. Drinking temperature influences furan and furan derivative exposure. Cup choice affects cooling dynamics but not temperature dependent furan exposure. Abstract: This study examined the influence of consumer behavior on furan, 2-methylfuran, 3-methylfuran, 2, 5-dimethylfuran and 2, 3-dimethylfuran exposure in coffee. Coffees brewed using a filter, fully automatic, capsule machine or reconstituted instant coffee were found to have a significant different cup concentrations of furan derivatives. Coffee brewed with the fully automatic machine contained the highest furan and furan derivative concentrations (99.05 µg/L furan, 263.91 µg/L 2-methylfuran, 13.15 µg/L 3-methylfuran and 8.44 µg/L 2, 5-dimethylfuran) whereas soluble coffee did not contain detectable levels, thereby contributing least to a consumer's dietary exposure. Furan and furan derivative concentrations were found to decrease significantly upon cooling, reducing consumer exposure by 8.0–17.2 % on average once the coffee reached drinking temperature 55–60 °C, in ceramic cups. Serving coffee in a ceramic or disposable cup were found to influence the cooling dynamics of the coffee but did not statistically influence the consumers exposure at a given temperature.